Signaling underlying kappa opioid receptor-mediated behaviors in rodents - Liu-Chen, Lee-Yuan; Huang, Peng (Frontiers in Neuroscience, 2022)
Kappa opioid receptor (KOR) agonists are potentially useful as analgesic and anti-pruritic agents, for prevention and treatment of substance use disorders, and for treatment of demyelinating diseases. However, side effects of KOR agonists, including psychotomimesis, dysphoria, and sedation, have caused early termination of clinical trials. Understanding the signaling mechanisms underlying the beneficial therapeutic effects and the adverse side effects may help in the development of KOR agonist compounds. In this review, we summarize the current knowledge in this regard in five sections. First, studies conducted on mutant mouse lines (GRK3-/-, p38alpha MAPK-/-, β-arrestin2-/-, phosphorylation-deficient KOR) are summarized. In addition, the abilities of four distinct KOR agonists, which have analgesic and anti-pruritic effects with different side effect profiles, to cause KOR phosphorylation are discussed. Second, investigations on the KOR agonist nalfurafine, both in vitro and in vivo are reviewed. Nalfurafine was the first KOR full agonist approved for clinical use and in the therapeutic dose range it did not produce significant side effects associated with typical KOR agonists. Third, large-scale high-throughput phosphoproteomic studies without a priori hypotheses are described. These studies have revealed that KOR-mediated side effects are associated with many signaling pathways. Fourth, several novel G protein-biased KOR agonists that have been characterized for in vitro biochemical properties and agonist biases and in vivo behavior effects are described. Lastly, possible mechanisms underlying KOR-mediated CPA, hypolocomotion and motor incoordination are discussed. Overall, it is agreed upon that the analgesic and anti-pruritic effects of KOR agonists are mediated via G protein signaling. However, there is no consensus on the mechanisms underlying their side effects. GRK3, p38 MAPK, β-arrestin2, mTOR pathway, CB1 cannabinoid receptor and protein kinase C have been implicated in one side effect or another. For drug discovery, after initial in vitro characterization, in vivo pharmacological characterizations in various behavior tests are still the most crucial steps and dose separation between beneficial therapeutic effects and adverse side effects are the critical determinant for the compounds to be moved forward for clinical development.